Numerical Modeling of Traditional Masonry Walls Strengthened with Grout Injection - Doran, Bilge; Yuzer, Nabi; Aktan, Selen; Oktay, Didem; Ulukaya, Serhan (TAYLOR & FRANCIS INC, 2020)
The main purpose of this article is to experimentally and numerically study the improvements introduced by the grout injection strengthening technique for the structural rehabilitation of traditional unreinforced masonry (URM) walls. In this context, four damaged URM walls with four different types of lime mortars under shear-compression are strengthened using grout injection method. Injection materials (Grout) which have same contents with existing mortar types are applied to all cracks in damaged walls. Besides, for the numerical simulations, a simplified micro modeling strategy is preferred combining the mortar and the mortar-unit interface behavior and then an elasto-plastic damage (EPD) approach is adopted calibrating the parameters of Oliver's damage model and the modified von-Mises yield criterion for the masonry constituents. Results show that the proposed approach can be useful to describe the behavior of mortar and mortar-unit interface in strengthened masonry structures with grout injection.
Keywords: Damage model; elasto-plastic behavior; finite element analysis; grout injection; masonry walls; traditional lime mortars; INPLANE BEHAVIOR; SHEAR; MORTARS; COMPRESSION; Architecture; Construction & Building Technology; Engineering